2016
DOI: 10.1016/j.puhe.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Young people's exposure to point-of-sale tobacco products and promotions

Abstract: POS displays remain a key vector in most countries for advertising tobacco products, and it is important to develop robust measures of exposure. The data reported in this paper provide a baseline measure for evaluating the efficacy of legislation prohibiting such displays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
4
35
0
Order By: Relevance
“…Scotland showed that both for supermarkets and small shops 80% of adolescents recalled seeing tobacco products or promotions. 12 Only banning displays in supermarkets is therefore not sufficient and our findings support the need for comprehensive bans on tobacco display in countries where tobacco is still visible at POS.…”
Section: Research Papersupporting
confidence: 49%
See 2 more Smart Citations
“…Scotland showed that both for supermarkets and small shops 80% of adolescents recalled seeing tobacco products or promotions. 12 Only banning displays in supermarkets is therefore not sufficient and our findings support the need for comprehensive bans on tobacco display in countries where tobacco is still visible at POS.…”
Section: Research Papersupporting
confidence: 49%
“…'), ranging from every day to never, as used previously. 12 Students could also opt for 'don't know'. Shop types that were likely to sell tobacco were categorised into small shops and large shops, with small shops including: newsagents/corner shops, garage shops/petrol stations, grocery shops or mini marts, fish and chip shops, and other takeaway shops.…”
Section: Shop Visit Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…16 Further details of the retail audits and how shops were identified are given in previous publications. 8,22 Observers worked in pairs to conduct the audits which were undertaken discreetly without retailer's being aware. Data collection was facilitated by a token purchase made in each retail outlet to gain access to the tobacco counter, and the use of memory aids and devices, such as mobile phones to record key numeric data (eg, number of stor- age unit shelves).…”
Section: Retail Audit Methodsmentioning
confidence: 99%
“…Attracting consumers’ attention to POS displays is certainly a goal of tobacco companies. Power walls are designed to be maximally eye-catching, and tobacco companies pay large sums of money to have the power wall appear in the most prominent in-store locations (e.g., behind the cashier; often close to products intended for children; Stead et al, 2016). …”
Section: Introductionmentioning
confidence: 99%